Examining personal and altruistic fear of ransomware - Maher, Cooper A. (Scams, cons, frauds, and deceptions, 2024)
Despite the growth in literature examining fear of cybercrime, few studies have examined altruistic fear online. Additionally, few studies have examined ransomware fear, potentially limiting the effectiveness of fear reduction policies. Using randomly assigned vignettes administered to online samples (n = 428; 432), findings indicate that perceptions of disorder were associated with increased personal fear, yet were not associated with altruistic ransomware fear. Social cohesion was associated with altruistic fear, yet was not associated with personal fear. Findings demonstrate the need for fear reduction policies to acknowledge the multifaceted nature of fear and adapt explanatory models to online contexts.